HOMESTAY SEBAGAI PENGEMBANGAN USAHA MASYARAKAT DI DESA WISATA KEMBANG KUNING KABUPATEN LOMBOK TIMUR - Ratmaja, Lalu; Pattaray, Anas (Ministry Of Tourism, 2019)
Kembang Kuning tourism village is a tourism village in East Lombok Regency with an advantage at the foot of Mount Rinjani in the south and has local potential that can be an attraction for tourists. The existence of this tourist village is an opportunity for residents to provide homestay for tourists. In addition to being an accommodation offered, homestay is also a business opportunity for residents. The homestay business for the community is used as additional livelihood after agriculture, for that it needs in-depth research to find out more about the condition of the homestay in the Kembang Kuning Tourism Village. Therefore, this study aims to analyze homestay businesses in the Kembang Kuning Tourism Village seen from 3 (three main components of this business program, namely institutions, actors and products. The research method used in this study is a qualitative method with data collection methods in the form of interviews The results of this study illustrate the homestay business program seen from the local institutions shown by the existence of a local organization that regulates tourism activities, Pokdarwis Lingko` Cave, which supervises homestay business actors who are self-supporting communities in the Kembang Kuning Tourism Village. This homestay produces products offered as attractions that are the reason for tourists to come in the form of homestays and activities that become tourist attractions.The results of this analysis form the basis for preparing recommendations for homestay businesses viewed from the three components.Keywords: Tourism, Kembang Kuning Tourism Village, Homestay Business